Impact of Strain Variation of Dichelobacter nodosus on Disease Severity and Presence in Sheep Flocks in England - Monaghan, Emma M.; Prosser, Naomi S.; Witt, Jessica; Lewis, Katharine E.; Nabb, Elizabeth; Keeling, Matt J.; Purdy, Kevin J.; Green, Laura E. (Frontiers in Veterinary Science, 2021)
AprV2 and aprB2 are variants of the apr gene of Dichelobacter nodosus, the cause of footrot in sheep. They are putative markers for severe and mild disease expression. The aim of our study was to investigate the distribution of aprV2 and aprB2 in flocks with and without footrot. Our hypotheses were that both strains are present in endemically affected flocks, with aprB2 and aprV2 associated with mild and virulent phenotypes respectively but that D. nodosus is not present in flocks without footrot. Alternatively, aprB2 persists in flocks without footrot. Despite extensive searching over three years only three flocks of sheep without footrot were identified. D. nodosus was not detected in these three flocks. In one further flock, only mild interdigital dermatitis was observed, and only aprB2 was detected. Twenty-four flocks with endemic footrot of all severities were sampled on three occasions and all were positive for D. nodosus and the aprV2 variant; aprB2 was detected in only 11 of these flocks. AprB2 was detected as a co-infection with aprV2 in 22% of samples and was more likely in mild footrot phenotypes than severe. D. nodosus serogroups were not associated with footrot phenotype. We conclude that D. nodosus, even aprB2 strains, do not persist in flocks in the absence of footrot. Our results support the hypothesis that aprB2 is associated with mild footrot phenotypes. Finally, we conclude that given the small number of flocks without footrot that were identified, footrot is highly endemic in English sheep flocks.